Low dietary calcium intake leads to a higher colorectal cancer burden in countries with low social development: findings from the Global Burden of Disease Study 2021 - Wu, Junhong; Zhang, Ziyi; Chen, Jiong; Yu, Shiya; Liu, Donglin; Jiang, Junhui; Liu, Tingting; Zhao, Hu; Wang, Yu (Frontiers in Nutrition, 2025)
BackgroundNumerous studies have demonstrated that individuals with low calcium intake are at increased risk of developing colorectal cancer (CRC), and calcium intake exhibits significant global variation. However, a comprehensive analysis of the diet low in calcium-attributable colorectal cancer (DLCACRC) disease burden remains lacking.ObjectiveThis study aimed to investigate the global distribution and temporal trends of DLCACRC from 1990 to 2021, providing evidence to support the development of evidence-based nutrition policies. Methods: Data on deaths, disability-adjusted life years (DALYs), mortality rates, and DALYs of DLCACRC between 1990 and 2021 were extracted from the GBD database. Age-standardized data were utilized to facilitate comparisons across regions and countries. Joinpoint regression analysis was conducted to assess temporal patterns in disease burden. Estimated annual percentage changes (EAPCs) were calculated to quantify the rate of change in relevant indicators. Pearson correlation analysis was performed to determine the relationship between the disease burden and the Social Development Index (SDI).ResultIn 2021, the global age-standardized mortality rate (ASMR) of DLCACRC reached 1.06 (95% CI: 0.77–1.33), while the age-standardized disability-adjusted life year rate (ASDR) was 24.7 (95% CI: 18.17–31.02). These metrics demonstrated a downward trend, showing 31.3 and 33.3% reductions, respectively, compared to 1990. The most rapid reductions in ASMR and ASDR were occurred during 2004 and 2007, with annual percentage change (APC) of −2.12 (95% CI: −2.80–1.43) and −2.29 (95% CI: −2.92–1.65), respectively. Significant differences in disease burden were observed across countries and regions, with Southeast Asia reporting the highest ASMR and ASDR of DLCACRC. At the national level, Zambia recorded the highest ASMR and ASDR. Women experienced a higher disease burden than men, and the disease burden was positively correlated with age.ConclusionFrom 1990 to 2021, the global disease burden of DLCACRC declined, although substantial regional disparities persist. Governments in these regions should adopt targeted strategies to enhance calcium intake among residents, thereby alleviating the disease burden. Particular attention should be given to women and older adults.